1997
DOI: 10.1002/(sici)1097-0339(199701)16:1<1::aid-dc2>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Atypical squamous cells of undetermined significance: Correlative histologic and follow‐up studies from an academic medical center

Abstract: The diagnosis of ASCUS (atypical squamous cells of undetermined significance) was introduced in the 1988Bethesda System for reporting cervical/vaginal cytologic findings. Outcome and appropriate management of patients with this diagnosis is not presently established. Criteria defining ASCUS are nuclear enlargement (2.5-3.0 times normal intermediate cell nucleus), mild nuclear hyperchromasia, smooth nuclear outlines with mild variation in nuclear size and shape, or else two, but not all three, cytologic criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
33
6
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 4 publications
10
33
6
4
Order By: Relevance
“…Patients with initial ASCUS diagnoses showed SIL on follow-up in 30% of cases in the current study and corroborated previous studies [21][22][23] in which follow-up of ASCUS cases showed SIL rates of 34.7%, 49%, and 66.7%, respectively. Although there is interobserver variability in the diagnosis of ASCUS, 24 a diagnosis of ASCUS in the sexually active adolescent population has significant implications for the development of definite precursor cervical neoplasia.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with initial ASCUS diagnoses showed SIL on follow-up in 30% of cases in the current study and corroborated previous studies [21][22][23] in which follow-up of ASCUS cases showed SIL rates of 34.7%, 49%, and 66.7%, respectively. Although there is interobserver variability in the diagnosis of ASCUS, 24 a diagnosis of ASCUS in the sexually active adolescent population has significant implications for the development of definite precursor cervical neoplasia.…”
Section: Discussionsupporting
confidence: 92%
“…This rate is lower in comparison with other studies done for ASCUS. [8][9][10][11][12][13] This is a subset of patients in which repeat a smear prior to biopsy, if persistent abnormality is encountered, is recommended by the National Health Service Cervical Screening Programme 14 document and CAP. 9 …”
Section: Atypical Cellular Abnormalitiesmentioning
confidence: 99%
“…A range of outcomes has been found that generally centers around ASCUS being predictive of viral changes or dysplasia in 25-55% (the average of 12 studies was 34%) of cases and high-grade squamous intraepithelial lesions (HGSIL) in about 5-20% of cases (average, 9%), depending on the mechanism of follow-up. [2][3][4][5][6][7][8][9][10][11][12][13][14] These data have warranted increased attention to follow-up in ASCUS patients. 15 Due to demographics in the USA and the nature of cervical cancer, the majority of women participating in Papanicolaou (Pap) smear screening are under age 50.…”
mentioning
confidence: 99%